Identification of Functional Group Compound in Nginang Process: Ethnochemistry-Based Teaching Module for High School - Firmansyah, Dodiy; Siahaan, Jacksoon; Supriadi, Supriadi; Ariani, Sunniarti; Adiguna, Sya'ban Putra (Jurnal Biologi Tropis, 2024)
The Nginang process is one of the Sasak tribe's cultures that can be integrated into sasambo ethnochemical learning. The basic ingredients of the betel chewing process consist of betel leaves, lime, and areca nuts. These ingredients contain organic compounds that are identified as including hydroxyl (-OH) and carbonyl (C=O) groups. This study seeks to identify the functional groups present in betel leaves, areca nuts and residues after the betel chewing process in the functional group area and fingerprint area. The identification of organic compounds in this study was conducted through three stages: (1) grinding the "betel chewing" material, namely the refining and sieving process using 100 mesh; (2) washing using ethyl acetate and (3) functional group analysis using Fourier Transform Infrared Spectroscopy. Based on the results of the Fourier Transform Infrared Spectroscopy analysis of betel leaves, areca nuts, and residue after chewing betel in the functional group area containing -OH groups respectively at wave numbers 3165.73 cm-1, 3280.67 cm-1 and 3406.03 cm-1, the C=O group shows peaks at wave numbers 1728.86, 1649.00, and 1728.08 cm-1, while in the fingerprint area the C-O group appears at wave numbers 1059.61, 1056.89, and 1056.80 cm-1.